2009
DOI: 10.1002/elan.200804543
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanograins Incorporated PEDOT Modified Electrode for Electrocatalytic Sensing of Hydrogen Peroxide

Abstract: A silver nanograins (Ag NGs ) incorporated poly [3,4-ethylenedioxythiophene] (PEDOT) modified electrode was prepared by a simple electrochemical method without using any stabilizer or reducing agent. The surface morphology and thickness of the resulting modified electrode was characterized by using AFM. It was found that the size of the silver particles in the PEDOT modified electrode was smaller than that in the bare electrode. AFM studies also revealed that Ag NGs were uniformly distributed in the PEDOT mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…In another study [36] with the polymer 5,2´:5´,2"-terthiophene-3´-carboxylic acid polymer (TCAP)), also with HRP, hydrogen peroxide reduction was measured at -0.2 V vs. Ag/AgCl and the response was more sensitive (0.48 μA cm -2 mmol -1 dm 3 ), with a wider linear range (up to 1.5 mmol dm -3 ) but the detection limit of 0.2 mmol dm -3 ) was higher than in the present work. There are very few reports in the literature concerning the determination of hydrogen peroxide without enzyme amplification at electrodes modified with conducting polymers [37] or composites containing polymer [38];…”
Section: Determination Of H 2 O 2 At Pedot/pnr Modified Electrodementioning
confidence: 99%
“…In another study [36] with the polymer 5,2´:5´,2"-terthiophene-3´-carboxylic acid polymer (TCAP)), also with HRP, hydrogen peroxide reduction was measured at -0.2 V vs. Ag/AgCl and the response was more sensitive (0.48 μA cm -2 mmol -1 dm 3 ), with a wider linear range (up to 1.5 mmol dm -3 ) but the detection limit of 0.2 mmol dm -3 ) was higher than in the present work. There are very few reports in the literature concerning the determination of hydrogen peroxide without enzyme amplification at electrodes modified with conducting polymers [37] or composites containing polymer [38];…”
Section: Determination Of H 2 O 2 At Pedot/pnr Modified Electrodementioning
confidence: 99%
“…The αn α was calculated to be 0.445, it meant that the rate-determining step was one electron transfer progress because the value of α ranges between 0.3 and 0.7. According to the literature, [45] the mechanism for H 2 O 2 electro-reduction may be expressed as follows:…”
Section: Electrochemical Characteristics Of the Sensormentioning
confidence: 99%
“…To the best of our knowledge, the usage of MES as a modifier for the fabrication of HP sensor had never been reported until our recent work. On the other hand, polymers films have been proven to be suitable matrices for dispersing metallic nanomaterial, and the composites of polymer and metal nanomaterial can exhibit some new properties than polymer or metal nanomaterial alone [25,[36][37][38][39]. Chen et al [25] reported a HP sensor based on silver nanograins incorporated poly(3,4-ethylenedioxythiophene) modified electrode.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, polymers films have been proven to be suitable matrices for dispersing metallic nanomaterial, and the composites of polymer and metal nanomaterial can exhibit some new properties than polymer or metal nanomaterial alone [25,[36][37][38][39]. Chen et al [25] reported a HP sensor based on silver nanograins incorporated poly(3,4-ethylenedioxythiophene) modified electrode. Zhang et al [39] fabricated an amperometric HP sensor based on the silver nanoparticles/poly(alizarin yellow R) modified electrode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation